(untitled) (مجلة الواحات للبحوث والدراسات, 2025)
Sleep Rhythm Disorders Are Among The Most Common Sleep Disorders Among People, And This Disorder May Arise As A Result Of The Complexities Of Life Demands That Lead To Psychological And Social Pressures, Thus Failing To Meet An Individual’s Need For Sleep, Which In Turn Affects The Nervous System And Consequently The Whole Body. Therefore, Sleep Plays A Crucial Role In The Overall Health Of Individuals. This Study Aims To Understand The Impact Of Circadian Rhythm Disorders On The Mental And Physical Health Of Individuals, Using A Descriptive-Analytical Approach To Answer The Study Questions, Which Include: What Is The Concept Of Circadian Rhythm Disorder? What Are Its Types? What Is The Impact Of Circadian Rhythm Disorder On Individuals’ Mental Health? Keywords: Circadian Rhythm Disorders, Sleep Rhythm Disorder, Mental Health, Physical Health, Individuals.